Efeitos da modulação mecânica induzida pela depleção do colesterol de membrana nos mecanismos de reparo celular - Natália Fernanda do Couto (2016)
Membrane repair after injury is an important process in retaining cell integrity, especially for cells which are under constant physical stress, such as endothelial cells. However, changes in the mechanical properties of membranes, such as those observed after cholesterol depletion, could impair the ability of cells in repairing injured membrane, and so contribute to endothelial fragility. The goal of this work was to evaluate the influence of the mechanical modulation induced by cholesterol depletion, upon MCD treatment, on membrane repair mechanisms. All the experiments were performed using a cell lineage of a human umbilical vein endothelial cell (EAhY926). As previously observed by our group, the absence of cholesterol leads to a reorganization of cellular actin and de novo polymerization, an increase in cell rigidity, as well as an induction of a rapid event of lysosomal exocytosis as early as 10 minutes after MCD exposure. Additionally, during cholesterol sequestration, we observed an increase in endocytic events between 10-20 minutes which coincided with the peak of exocytosis, indicating that these are most likely compensatory endocytic events triggered by lysosomal exocytosis. In parallel, we observed that constitutive endocytic events, arising from pinocytic processes which are common in these cells, is blocked upon cell treatment with MCD, suggesting that the reorganized cytoskeleton could function as a mechanical barrier to pinocytic events. Also, coinciding with the peak of cell rigidity induced by MCD treatment, cells become more prone to mechanical membrane injury in relation to non-treated cells. Together, these data show that mechanical modulation induced by cholesterol depletion not only alters membrane traffic in cells, but also makes cells more susceptible to mechanical injury.